(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
EAP course teaches how the program concerns and provides us with a valuable way of organizing our thinking about conceptual disciplinary within the particular community. The area of EAP is referred with genres. The process of writing academically requires creating a text where the writer takes it for granted the reader is about to recognize. To group texts together, writers utilize language in order to respond to recurring situations and this case is +represented with the term genre.